1983
DOI: 10.1037/h0080701
|View full text |Cite
|
Sign up to set email alerts
|

Canadian prime ministers: Complexity in political crises.

Abstract: This paper examines the reactions of three Canadian prime ministers to major domestic crises. Previous laboratory research has shown that environmental stress leads to decreases in integrative complexity among decision-makers. Studies of documents related to historical events have focused on the behaviour of leadership groups in international crises. The current data support the hypothesis of a stress-related decrease in a different context. The integrative complexity of speeches given by Sir John A. Macdonald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…This cognitive construct has proven valuable in understanding the performance, ideology, and decision making of United States presidents (Tetlock,198Ib), senators (Tetlock, 198la, 1983;Tetlock, Hannum, & Micheletti, 1984), and Supreme Court justices (Tetlock, Bernzweig, & Gallant, 1985); prominent participants in the slavery debate in antebellum America (Tetlock, Armor, & Peterson, 1994); British parliamentarians (Tetlock, 1984) and Canadian prime ministers (Ballard, 1983;Ballard & Suedfeld, 1988); members of the Soviet Politburo (Tetlock & Boettger, 1989); European diplomats (M. D. Wallace & Suedfeld, 1988); and successful and unsuccessful revolutionaries (Suedfeld & Rank, 1976). This research has made a convincing case that human informationprocessing complexity has tremendous consequences for political ideology and leader performance.…”
Section: Extrinsic Rationalesmentioning
confidence: 99%
“…This cognitive construct has proven valuable in understanding the performance, ideology, and decision making of United States presidents (Tetlock,198Ib), senators (Tetlock, 198la, 1983;Tetlock, Hannum, & Micheletti, 1984), and Supreme Court justices (Tetlock, Bernzweig, & Gallant, 1985); prominent participants in the slavery debate in antebellum America (Tetlock, Armor, & Peterson, 1994); British parliamentarians (Tetlock, 1984) and Canadian prime ministers (Ballard, 1983;Ballard & Suedfeld, 1988); members of the Soviet Politburo (Tetlock & Boettger, 1989); European diplomats (M. D. Wallace & Suedfeld, 1988); and successful and unsuccessful revolutionaries (Suedfeld & Rank, 1976). This research has made a convincing case that human informationprocessing complexity has tremendous consequences for political ideology and leader performance.…”
Section: Extrinsic Rationalesmentioning
confidence: 99%
“…Previous research using a different measure, integrative complexity, found leaders demonstrating more complexity when stress was absent and less when stress was present (Ballard 1983;Porter and Suedfeld 1981; and that public statements by multiple officials of nations that experienced surprise attacks showed more complexity before the attack and less immediately afterward (Suedfeld and Bluck 1988).…”
Section: Moral Reasoning Stagementioning
confidence: 97%
“…Instead, they made poor decisions that aggravated rather than ameliorated the crisis. To explore this process further, several investigators have applied content analytical techniques to historical documents in order to gauge the conceptual (or "integrative") complexity of the decision makers (e.g., Ballard, 1983;Suedfeld, Wallace, & Thachuk, 1993). These studies repeatedly demonstrate that the outbreak of violence during a major crisis can be predicted if conceptual complexity decreases rather than increases (Raphael, 1982;Suedfeld, Tetlock, & Ramirez, 1977).…”
mentioning
confidence: 98%